Co-movement Between the US and Hong Kong Interest Rates under the Linked Exchange Rate System: การเคลื่อนไหวร่วมระหว่างอัตราดอกเบี้ยสหรัฐและฮ่องกงภายใต้ระบบอัตราแลกเปลี่ยน แบบ Linked Exchange Rate System - Sapwarobol, Teerasak (Journal of Applied Economics and Management Strategy, 2022)
บทคัดย่อ งานวิจัยนี้ทำการทดสอบการเคลื่อนไหวร่วมระหว่างอัตราดอกเบี้ยของฮ่องกงและสหรัฐเพื่อดูประสิทธิภาพของกลไกการปรับตัวของอัตราดอกเบี้ยของฮ่องกงในช่วงก่อนและหลังการปฎิรูประบบ Linked Exchange Rate System ภายใต้กลไก Convertibility Zone ข้อมูลที่ใช้ในการศึกษาเป็นข้อมูลทุติยภูมิประเภทอนุกรมเวลารายเดือนในช่วงปี พ.ศ. 2540–2562 โดยทำการทดสอบการเคลื่อนไหวร่วมระหว่างอัตราดอกเบี้ยของฮ่องกงและสหรัฐ 3 ประเภท ได้แก่ 1) อัตราดอกเบี้ยเงินให้กู้ยืมระหว่างธนาคารอายุ 3 เดือน 2) อัตราดอกเบี้ยเงินให้กู้ยืมระหว่างธนาคารอายุ 12 เดือน และ 3) อัตราผลตอบแทนพันธบัตรรัฐบาลอายุ 10 ปี ตามวิธีการของ Johansen Cointegration ผลการศึกษาไม่พบการเคลื่อนไหวร่วมระหว่างอัตราดอกเบี้ยของฮ่องกง และสหรัฐในช่วงก่อนการปฎิรูประบบอัตราแลกเปลี่ยนในทุกกรณี แต่ภายหลังการปฎิรูประบบอัตราแลกเปลี่ยน พบว่าอัตราดอกเบี้ย HIBOR 3 เดือนมีการเคลื่อนไหวร่วมไปกับอัตราดอกเบี้ย LIBOR 3 เดือนอย่างมีนัยสำคัญทางสถิติ สะท้อนให้เห็นว่าการปฎิรูประบบอัตราแลกเปลี่ยนภายใต้กลไก Convertibility Zone ในปี พ.ศ. 2548 มีส่วนช่วยทำให้กลไกการปรับตัวของอัตราดอกเบี้ย HIBOR 3 เดือนเป็นไปอย่างมีประสิทธิภาพมากยิ่งขึ้น ABSTRACT This study aimed to examine the co-movement of the interest rates between Hong Kong and the US in order to observe effectiveness of Hong Kong’s interest rate adjustment mechanism, before and after the refinement of Linked Exchange Rate System under Convertibility Zone. Monthly time-series data during 1997-2019 were utilized to examine co-movement of 3 types of interest rates; i.e., 1) 3-month interbank rate, 2) 12-month interbank rate, and 3) 10-year government bond yield, following Johansen cointegration methodology. The results revealed that, before the refinement of Linked Exchange Rate System, Hong Kong interest rates did not cointegrate with the US interest rates in all cases. Yet, after the refinement of Linked Exchange Rate System, the results revealed the co-movement between 3-month HIBOR and 3-month LIBOR with a high degree of statistical significance. This reflected that the refinement of Linked Exchange Rate System under Convertibility Zone in 2005 help improve effectiveness of Hong Kong’s 3-month HIBOR adjustment mechanism.